Reduction of Carbon Emission Is Optimized During the Life Cycle of Commonly Used Force Main Pipe Materials - Alsadi, Alhossin A.; Matthews, John C. (Frontiers in Water, 2022)
With increasing attention to global warming and greenhouse gas (GHG) emissions and providing a better environment for coming generations, there is a critical need to quantify and decrease the environmental impact. Underground construction projects are one of the biggest constructions in North America; consequently, it is one of the GHG emissions' primary sources. This research focused on optimizing the carbon dioxide (CO2) emissions for a 91 cm (36 in) diameter sewer pressure pipe with 3 m (10 ft) depth and 30 m (100 ft) length, operating at 690 kPa (100 psi) during the commonly used pipeline materials' life cycle: Cured-in-Place Pipe (CIPP), Pre-stressed Concrete Cylinder Pipe (PCCP), High-density polyethylene (HDPE) pipe, and Polyvinyl Chloride (PVC) pipe. The life operations for this study were considered 100-years. The four phases of a pipeline life cycle included in this study are fabrication, installation, operation, and disposal phases. Life cycle assessment (LCA) is a methodology to evaluate the environmental impacts of products or service systems throughout the complete life cycle from the cradle to the grave. The study results show that the CO2 emissions have been reduced by 16% on the PCCP pipe, 4% on PVC pipe, 1% on HDEP pipe, and by 3.2% and 2.0% on CIPP lining (50 years and 100 years life expectancy, respectively). It is recommended that field studies be conducted in future research to obtain the necessary data to overcome the dependence on assumptions made in this study. Also, I recommended including the direct and social costs, which will make the decision easier for engineers and decision-makers to choose the right choice.